Effectiveness of calcium hydroxide-based intracanal medicaments against Enterococcus faecalis - Lima, R. K. P. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Faria-Junior, N. B. [UNESP]; Tanomaru-Filho, M. [UNESP] (Wiley-Blackwell, 2012)
Aim To evaluate the antimicrobial efficacy of calcium hydroxide-based intracanal medicaments against Enterococcus faecalis. Methodology One hundred and six single-rooted human teeth were inoculated with E. faecalis (ATCC 29212) and incubated in an microaerophilic environment for 21 days. Teeth were divided according to the medicaments and period: G1 Calen (7 days); G2 Calen (14 days); G3 Calen/camphorated paramonochlorophenol (CMCP) (7 days); G4 Calen/CMCP (14 days); G5 Calen/0.4% chlorhexidine (CHX) (7 days); G6 Calen/0.4% CHX (14 days); G7 Calen/1% CHX (7 days); G8 Calen/1% CHX (14 days); G9 chemo-mechanical preparation with no medication and G10 no chemo-mechanical preparation and no medication. Microbial samples were harvested immediately after removal of the intracanal dressing and 7 days later. Data were subjected to anova (P < 0.05). Results All medicaments were associated with a reduction in E. faecalis after removal of the dressing (post-medication harvest). However, all specimens were associated with an increase in CFU mL-1 values after 7 days (final harvest). Calen/CMCP and Calen/CHX had the lowest CFU mL-1 values (P < 0.05). Conclusion In this laboratory study using extracted teeth all calcium hydroxide-based medicaments were able to significantly reduce the CFU mL-1 values of E. faecalis in the root canal system.
Keywords: calcium hydroxide; Enterococcus faecalis; intracanal medication